A Comparative Study of the US-China Trade War Impacts on Canada, Australia, and Vietnam - Badriyatus Salma; Febrianti Nur Qothimah; Arvito Rachman; Ferdian Ahya Al Putra (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
The US-China trade war is a trade conflict that has an impact on the global economy. In this trade war, the hegemon state becomes the main global focus. Therefore, the US-China trade war reflects the rivalry between two superpowers that influence global economic stability. This trade war creates uncertainty for economies around the world. This research examines the concept of hegemonic stability theory in the US-China trade war which reflects the rivalry between hegemons. This research uses a qualitative descriptive method. This research also uses the theory of hegemonic stability in the international system. Moreover, this research used literature study techniques to obtain relevant data. The results show that the US-China trade wars have an impact on the global economy. This study finds that Canada and Australia suffer from trade disruption, while Vietnam benefits from investment diversion. The emergence of China as a new and great economic power proves the hegemonic stability though, that a world with more than one dominant player causes chaos, especially in the world economy.